Process Standardization on An Assembly Line: A Case Study At A Multinational Machine Manufacturer - Cassiano Rodrigues Moura; Cristiane Ceratti Nunes (GEPROS: Gestão da Produção, Operações e Sistemas, 2019)
Companies are concerned about securing their space in the market, and this demands more and more that their products are of high quality, with a smaller and smaller lead time. An alternative to achieve this goal is to optimize your production process. Therefore, the objective of this work is to standardize the assembly process of a group of components in a multinational machine manufacturer. The methodology employed in this study is bibliographic through Lean Manufacturing and Standardized Work, used as tools for the standardization for developing the Process Plan, Control Plan and PFMEA, thus constructing a new assembly process for those involved. These changes resulted in an improvement in the manufacturing and assembly processes of the selected group, reducing its assembly steps, cost and lead time, thus guaranteeing process reliability. The results show a 7% reduction in assembly costs, equivalent to R $ 14,500.00 less in the annual purchases of the pilot group.